Note—Gains from International Dual Listing - Yagil, Joseph; Forshner, Zivan (Management Science, 1991)
This study presents an attempt to explain how international dual listing of securities can reduce the effects of segmented international markets. By applying the mean-variance model we show that, for a return generating process given by the maximum distribution, the expected return on the dually listed security will be higher and the variance associated with it will be lower than for an otherwise identical (domestically) single listed security. This result appears to be consistent with the existence of dually listed securities in capital markets which are otherwise not integrated.